Determinants Of Covid-19 Vaccination Status In Communities In The Work Area Of Puskesmas Rawat Inap Karya Wanita In 2022: Determinan Status Vaksinasi Covid-19 Pada Masyarakat Di Wilayah Kerja Puskesmas Rawat Inap Karya Wanita Tahun 2022 - Siti Rohmah; Agus Alamsyah; Wulan Sari; Herlina Susmaneli; Sri Desfita (Badnur Medisa Group, 2022)
Karya Wanita Inpatient Health Center is one of the health centers with a lower vaccination coverage than other health centers, namely 9,768 doses of the 29,682 population to be vaccinated. The purpose of this study was to determine the determinants of the Covid-19 vaccination status in the community in the working area of ​​the Karya Wanita Inpatient Health Center in 2022. This type of research was Observational Quantitative Analytical with Cross Sectional Design. The population in this study was the general public in the working area of ​​the Karya Wanita Inpatient Health Center totaling ± 29,682. The sampling technique used consecutive sampling. The measuring instrument in data collection is a questionnaire. Data analysis was performed with univariate and bivariate (chi-square). The results showed that education (P-value = 0.002) POR = 3.145 (1.559-6.345), trust in hoax news (P-value = 0.001) POR = 4.501 (2.350-8.619), knowledge (P-value = 0.005) POR = 2,554 (1,361-4,793), attitude (P-value = 0.001) POR = 3,401 (1,798-6,432), and perception (P-value = 0,001) POR = 3,401 (1,798-6,432).The conclusion of this study is that there is a relationship between education, trust in hoax news, knowledge, attitudes and perceptions with Covid-19 vaccination status in community in the work area of ​​the Karya Wanita Inpatient Health Center in 2022. Suggestions for the Puskesmas to maximize education or dissemination of information directly related to the importance of Covid-19 vaccination and facts about the Covid-19 vaccine to all levels of society evenly.